Isolated Sphenoid Sinus lesions: a Tertiary Hospital Experience - Caetano, Mariana (2022)
Objective: To review and report isolated sphenoid sinus diseases from a tertiary hospital, with special attention to the patients' presenting symptoms, diagnosis, and clinical outcomes. Study Design, Material and Methods:Retrospective chart review performed on patients diagnosed with isolated sphenoid sinus disease, undergoing endoscopic sinus surgery between January 2017 and December 2021. Results: 19 patients were included, with a mean age of 48.0 ± 18.7 years. The most common symptom was headache (38.9%) followed by nasal obstruction (33.3%). Cranial neuropathies occurred exclusively in the group of malignant neoplasms. Inflammatory etiology was the most frequent (57.9%) and included fungal sinusitis (27%), chronic rhinosinusitis (18%) and mucocele (5%). Conclusions: The diagnosis of isolated sphenoid lesions requires a high degree of suspicion since they can present with nonspecific symptoms. Early surgical intervention, for diagnostic or therapeutic purposes, is generally indicated, with nasosinusal endoscopic surgery being the most appropriate modality in most cases.